1986
DOI: 10.1115/1.3143770
|View full text |Cite
|
Sign up to set email alerts
|

Model Reference Adaptive Control of Feed Force in Turning

Abstract: This paper applies the discrete-time single-input/single-output Model Reference Adaptive Control (MRAC) design technique of Landau and Lozano to the problem of regulating feed force on a lathe under varying cutting conditions. A first-order model is used to represent the relationship between feed force and the control input (feedrate). The MRAC scheme is implemented on a multi-microprocessor based computer-numerical-control system. Results of applying various algorithms derived from the MRAC design technique a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The relationship between the machining process force and the tool feed speed is nonlinear and time-varying, as shown in the following dynamic model (Landers & Ulsoy, 2000)  is 63% of the time required for a spindle revolution. (Daneshmend & Pak, 1986) Since m  is much smaller than the time constant of robot system, it is ignored here in the MRR controller design. Let,…”
Section: Process Force Modelmentioning
confidence: 99%
“…The relationship between the machining process force and the tool feed speed is nonlinear and time-varying, as shown in the following dynamic model (Landers & Ulsoy, 2000)  is 63% of the time required for a spindle revolution. (Daneshmend & Pak, 1986) Since m  is much smaller than the time constant of robot system, it is ignored here in the MRR controller design. Let,…”
Section: Process Force Modelmentioning
confidence: 99%
“…The relationship between the machining process force and the tool feed speed is nonlinear and time-varying, as shown in the following dynamic model (Landers & Ulsoy, 2000) 1  is 63% of the time required for a spindle revolution. (Daneshmend & Pak, 1986) Since m  is much smaller than the time constant of robot system, it is ignored here in the MRR controller design. Let,…”
Section: Process Force Modelmentioning
confidence: 99%
“…Early work has shown that these changes can lead to degradation in the performance of fixed-gain controllers, even to the point of instability [1]. To account for process variations and to maintain system stability, researchers in machining force control have employed adaptive control techniques (e.g., [2][3][4]). Recently, model-based approaches have been applied to the machining force control problem.…”
Section: Introductionmentioning
confidence: 99%